2023
DOI: 10.1038/s41467-023-38852-4
|View full text |Cite
|
Sign up to set email alerts
|

Scalable-produced 3D elastic thermoelectric network for body heat harvesting

Abstract: Flexible thermoelectric generators can power wearable electronics by harvesting body heat. However, existing thermoelectric materials rarely realize high flexibility and output properties simultaneously. Here we present a facile, cost-effective, and scalable two-step impregnation method for fabricating a three-dimensional thermoelectric network with excellent elasticity and superior thermoelectric performance. The reticular construction endows this material with ultra-light weight (0.28 g cm−3), ultra-low ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…With the advancement of thermoelectric science and technology, the morphology of weavable thermoelectric materials has become diverse, and the research focus in this field continues to evolve. Generally, research focus areas in weavable thermoelectrics can be categorized as indicated by figure 2, including 1D fibers [42,43, and nanowires (NWs) [167,168], 2D thin films [169][170][171][172], 3D fabrics [173][174][175][176][177][178][179][180][181][182][183][184][185][186], device assembling [42,43,124], simulations [187,188], and integrations [189]. Among them, thermoelectric fibers with typical 1D macroscopic morphologies have garnered significant research attention.…”
Section: Classifications Of Weavable Thermoelectricsmentioning
confidence: 99%
See 4 more Smart Citations
“…With the advancement of thermoelectric science and technology, the morphology of weavable thermoelectric materials has become diverse, and the research focus in this field continues to evolve. Generally, research focus areas in weavable thermoelectrics can be categorized as indicated by figure 2, including 1D fibers [42,43, and nanowires (NWs) [167,168], 2D thin films [169][170][171][172], 3D fabrics [173][174][175][176][177][178][179][180][181][182][183][184][185][186], device assembling [42,43,124], simulations [187,188], and integrations [189]. Among them, thermoelectric fibers with typical 1D macroscopic morphologies have garnered significant research attention.…”
Section: Classifications Of Weavable Thermoelectricsmentioning
confidence: 99%
“…Another research emphasis includes the design of substrates or supports that match woven thermoelectric fibers, such as common fabrics, flexible strings, and silicone. These support materials can serve solely as structural supports [173][174][175] or be thermoelectrically functionalized [176][177][178][179][180][181][182][183][184][185][186].…”
Section: Classifications Of Weavable Thermoelectricsmentioning
confidence: 99%
See 3 more Smart Citations